United States Securities Law - Open Textbook Library; eLangdell Press Editorial Staff (Open Textbook Library, 2014)
The United States Securities Code and Regulations appear in Title 15 of the United States Code and Title 17 of the Code of Federal Regulations. This publication was made with data provided by the United States government on the Office of Law Revision Counsel as well as the eCFR.
Due to the volume of the material, it has been divided up into eight volumes. -- Volume 1 -The Securities Act of 1933 and The Securities and Exchange Act of 1934 -- Volume 2 -The Investment Company Act of 1940 and The Investment Advisors Act of 1940 -- Volume 3 -Sarbanes-Oxley Act of 2002, Dodd-Frank Wall Street Reform Act and Consumer Protection Act of 2010 and Jumpstart our Business Startups Act of 2012 -- Volume 4 -Title 17 of the Code of Federal Regulations, Parts 200, 201, 202 and 203 -- Volume 5 -Title 17 of the Code of Federal Regulations, Parts 210 and 229 -- Volume 6 -Title 17 of the Code of Federal Regulations, Part 230 -- Volume 7 -Title 17 of the Code of Federal Regulations, Part 240 and 250 -- Volume 8 -Title 17 of the Code of Federal Regulations, Part 260, 270 and 275
In English.
Description based on print resource
Keywords: Law -- Textbooks -- United States; Contract Law -- Textbooks